1987
DOI: 10.1111/j.1151-2916.1987.tb05650.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Agglomerate Strength on Sintered Density for Yttria Powders Containing Agglomerates of Monosize Spheres

Abstract: The effect of agglomerate strength on sintered density, was determined for several yttria powders made by intentionally agglomerating 0.1‐μm, monodisperse yttrium hydroxycarbonate precursor spheres and calcining separate portions of the precursor at different temperatures to vary the strength of the intraagglomerate bonds. In this way, the effects of differences in particle morphology and other characteristics among the powders were minimized and the effect of agglomerate strength could be seen more clearly. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Ciftcioglu et al [18] investigated the effect of agglomerate strength on sintered density experimentally and achieved a conclusion that the sintered density of yttria powders decreased with increasing agglomerate strength. Rhodes [12] found that agglomerates limited attainable green density, interfered with the development of microstructure, impeded initial-stage sintering kinetics, and limited the potential benefit of fine crystallites in final-stage sintering.…”
Section: Introductionmentioning
confidence: 99%
“…Ciftcioglu et al [18] investigated the effect of agglomerate strength on sintered density experimentally and achieved a conclusion that the sintered density of yttria powders decreased with increasing agglomerate strength. Rhodes [12] found that agglomerates limited attainable green density, interfered with the development of microstructure, impeded initial-stage sintering kinetics, and limited the potential benefit of fine crystallites in final-stage sintering.…”
Section: Introductionmentioning
confidence: 99%
“…Since particle rearrangement is dominated by local forces, it is reasonable to assume that agglomerate rearrangement is also induced by the asymmetrical forces acting on each agglomerate. Agglomeration of particles has been observed and studied in many experiments [1,[18][19][20] and simulations [21,22]. Petzow et al [1] observed agglomeration during sintering of planar arrays of uniform copper spheres at 1 223 K. Similar phenomena have been found in irregular arrays of glass spheres [23], copper particles [12], compacts of fine tungsten powder [24], fine chromium oxide powder compacts [24] and alumina powder compacts [25].…”
Section: Introductionmentioning
confidence: 80%
“…Palmero et al [20] found a heterogeneous microstructure consist-ing of agglomerates of ultrafine alumina particles with size 150 nm-200 nm, which was sintered at 1 408 K. Kadusnikov et al have carried out several works [26][27][28] on agglomeration simulation using a sphere-polyhedron model. Ciftcioglu et al [18] investigated the effect of agglomerate strength on sintered density experimentally and made a conclusion that the sintered density of yttria powders decreased with increasing agglomerate strength. Martin et al [21] studied the morphology and strength of agglomerates through computer simulation and found that morphology of agglomerates has a clear effect on the tap density but the strength of agglomerates is a predominant factor affecting green density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneities are always present in green compacts and evolve during sintering (Lange, 1984;Ciftcioglu et al, 1987;Lim et al 2000). These heterogeneities (or "defects"), such as aggregates or large pores, are the source of microstructural defects which have a serious and detrimental influence on mechanical and thermo-mechanical properties of the material.…”
Section: Introductionmentioning
confidence: 99%